Til øjeblikkeligt brug! Brevduen som kommunikationsmiddel i det danske forsvar 1919-1945 - Nielsen, Jacob Vrist (Fra Krig og Fred, 2026)
‘For Immediate Use!’: The Homing Pigeon as Communication Channel in the Danish Defence, 1919-1945 Drawing on a complex and fragmentary archival source material, this article investigates why homing pigeons had their “golden age” in the first half of the 20th century, and which functions homing pigeons were to perform in the defence of Denmark. The analytical framework for the study is the defence preparations in Denmark and the General Staff's Intelligence Section who oversaw the military pigeon service. The article examines unexplored aspects of the defence preparations in Denmark, of Danish neutrality policy and of the relationship with neighbouring Germany both before and during the German occupation (1940-1945). Moreover, the article conveys new knowledge on the General Sta0 's Intelligence Section. The article shows that military authorities hazardously invested in the newest weapons and technologies, such as telecommunications, aircrafts, and submarines, that potentially increased war efficiency but at the same time were unfinished and unreliable. Modern warfare exhibited the weaknesses of the new technologies and created a demand for other low-tech alternatives and “reserve technologies”. The article argues that the homing pigeon – a millennia old and almost forgotten technology – had its golden age in modern warfare in the /rst half of the 20th century, because it could bridge the gaps, which arose due to the inefficiency of modern technologies. The war authorities did not just rediscover the homing pigeon, they also reinvented it and fused it with parachutes, missiles, and cameras, so that it could serve a range of new features that modern warfare necessitated.